COMPLICATIONS DURING HEMODIALYSIS IN END STAGE RENAL DISEASE PATIENTS IN A TEACHING HOSPITAL - Khan, Atta Muhammad; Afridi, Muhammad Abdur Rahman; Asghar, Muhammad; Ikram, Muhammad; Muhammad, Riaz (Journal of Postgraduate Medical Institute, 2019)
Objective: To determine the frequency of complications during hemodialysis in patients with end stage renal disease in Lady Reading Hospital, Peshawar. Methodology: A six months cross-sectional study of 219 end stage renal disease patients undergoing hemodialysis was conducted in the Departments of Medicine and Nephrology, Lady Reading Hospital, Peshawar, between October 2017 and March 2018. Relevant clinical and laboratory data pertaining to complications were collected and SPSS version 19 was used for data analysis. Results: Out of 219 patients, 145 (66.21%) were males. The mean age of patients was 55.8 ±7.67 yerars ( range 25 to 70 years). Complications were common in male patients (66.21%). During hemodialysis, the following complications were noticed; fatigue (80%); neuro-psychiatric complications include anxiety (60%), headache (58%), poor sleep (55%); infections like urinary tract infection (65%), central dialysis catheter infection (41.55%), HCV infection (16%), HBV infection (12%); gastrointestinal complications like deranged liver functions (58.4%), nausea (30%); various cardiovascular complications include pulmonary edema (60%), pericardial effusion (45%), hypertension (40%), sudden cardiac death (34%); hemodialysis equipment related complications (22%); and others like restless leg syndrome (32%) and anemia (20%). Conclusion: Most of the end stage renal disease patients on hemodialysis present with one or more complications and the most frequent were fatigue and neuropsychiatric complications.